The Interaction of Compensation on Intention to Stay and Perceived Organizational Support - Cindy Pramita; Sudarmiatin Sudarmiatin (Journal of Behavioral Economics, Finance, and Management Insights, 2025)
The increasingly fierce talent competition in the modern business ecosystem demands organizations, particularly Micro, Small, and Medium Enterprises (MSMEs), to formulate effective retention strategies to ensure operational sustainability. This study aims to systematically review the effect of compensation systems on employee intention to stay, by placing perceived organizational support (POS) as a moderating variable. The Systematic Literature Review (SLR) method is used with reference to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol through an in-depth analysis of literature in the Scopus database for the period 2015–2025.The study’s findings indicate that a competitive and fair compensation system is a key foundation for fostering employee retention intentions, but its effectiveness is highly dependent on the psychological factors of the work environment. Perceived Organizational Support (POS) has been shown to act as a significant moderator that strengthens this relationship; where employees’ perceptions of organizational care and appreciation transform the transactional value of compensation into deeper emotional bonds. The synergy between transparent reward policies and tangible organizational support creates human resource resilience, crucial for the long-term competitiveness of MSMEs. This study emphasizes the importance for MSME owners to focus not only on financial incentives but also on strengthening a culture of organizational support to reduce employee turnover rates in the era of digital transformation.